Improved Information Systems Model for Bangladesh - Jahangir Alam S.M.; Hu Guoqing; M. Rabiul Alam; Md. Golam Kibria; Md. Abdul Malek (Institute of Advanced Engineering and Science, 2014)
In the era of globalization, implementation of e-Government (e-Gov) is very crucial because it modernizes the public and private sector for the well being of people. To build the electronic based automatic governance for improving the quality of public services is the prime measure for implementation of e-Governance in Bangladesh. Interoperability is a key issue in implementing an e-Government system. To create a general platform for sharing and exchanging information among different institutions is essential for interoperability. Grid Computing based service could be a solution for resource sharing and interoperability of e-Gov systems. It is important to prepare standard policies and guidelines for e-Governance so that the desired expectations of interoperability between central and local government agencies can be achieved. Bangladesh government needs a specific policy which will deal with interoperability and ensure transparency and accountability in the Grid Computing Model.